TEKNIK ISOLASI DAN ELEKTROFORESIS DNA TOTAL PADA Kryptopterus apogon (Bleeker 1851) DARI SUNGAI KAMPAR KIRI DAN TAPUNG HILIR KABUPATEN KAMPAR PROVINSI RIAU - Dede Aryani Novitasari; Roza Elvyra; Dewi Indriyani Roslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Kryptopterus apogon is one of freshwater fish species that was only found in floodplain river in Riau Province. Many species of lais fish are found in Riau Province rivers and morphologically has the same shape therefore it is necessary to find alternative markers to distinguish the species. The important step in genetic analysis is DNA isolation. This study aimed to isolate the total DNA from Kryptopterus apogon. The fish samples were taken from the Kampar Kiri and Tapung Hilir rivers. Isolation of total DNA was done by taking the muscle tissue from the fish tail (1 mm x 1 mm in size). Isolation of total DNA was done using DNA isolation kit (QIAGEN DNeasy Blood & Tissue). After that, the total DNA was checked on 1% agarose gel to estimate the quantity and quality of total DNA. Total isolated DNA of Kryptopterus apogon from two rivers had various quality and quantity. Tha total quantity of DNA molecules ranged from to 100-200 ng/μl, while the total quality was good enough or not fragmented. The DNA was clear, thick, and no smear.